The General Limnology of Arctic Lakes as illustrated by Examples from Greenland. - Hansen, Kaj (Meddelelser om Grønland, 1967)
As the views of the limnology of arctic lakes up till now have almost exclusively been based on the observations of a few summer expeditions in Alaska and on the mountains in lower latitudes, the author has found it expedient in connexion with investigations into bottom samples from 16 lakes in North Greenland also to collect the great material of measurements distributed throughout the year which during the years 1954-57 were made by Dr. ULRIK RØEN. These observations of temperature, contents of oxygen, and electric conductivity, etc., together with investigations into the bottom samples show that the deep lakes in Northern Greenland are oligotrophic and very similar to the mountain lakes in Norway. The shallow lakes, on the other hand, show up to 65 per cent eutrophy. The surrounding rocks are also of importance for the biological type of the lakes, lakes in highly calcareous surroundings being just as eutrophic as normal Baltic lakes. The very short active biological period also exerts a strong influence on the chemical as well as the biological cycle of the lakes.